MOTIVASI GURU DALAM MEMEDIASI PROFESIONALISME GURU DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP PENINGKATAN KINERJA GURU - Happy Chirma Sya'roni (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
The purpose of this study was to examine and describe the professionalism, leadership, motivation, and performance of teachers at MAN 2 Bojonegoro. To examine and analyze the effect of professionalism and leadership on teacher motivation. To examine and analyze the effect of professionalism, leadership and motivation on teacher performance. To examine and analyze the effect of professionalism and leadership on teacher performance. The population in this study were the teachers of MAN 2 Bojonegoro, totaling 78 teachers. The sample in this study were 78 teachers who used a sampling technique with total sampling. The data collection technique in this study was a questionnaire. This study uses Partial Least Square (PLS)) analysis to test the hypothesis Teacher professionalism, leadership, motivation and teacher performance at MAN 2 Bojonegoro are included in the very high category. Professionalism and Leadership have a significant effect on motivation. Direct professionalism and direct leadership have no significant effect on teacher performance, while motivation has a significant effect on teacher performance. Professionalism and Leadership indirectly have a significant influence on teacher performance mediated by teacher work motivation.